Collaboration strategies and corresponding authorship in Agronomy research of Brazilian academic and non-academic institutions - de Souza Vanz, Samile Andréa; Gracio, Maria Claudia Cabrini [UNESP]; de Oliveira, Sandra Cristina [UNESP]; Chinchilla-Rodríguez, Zaida; Docampo, Domingo (Springer Nature, 2023)
Agricultural Sciences have become one of Brazil’s most efficient and sustainable research areas, where most publications benefit from scientific collaboration. The present study analyzes the influence of the designation as the corresponding author to researchers linked to Brazilian institutions on the impact of co-authored articles in the category Agronomy from the Web of Science for five-year periods from 2005 to 2019. We have observed a noticeable growth in the number of documents in collaboration between the five-year periods. However, international partnership in the area still needs to be improved, although it is higher in non-academic institutions. The study verified that the documents published by Brazilian authors with international colleagues present a higher normalized citation impact in all types of institutions and five-year periods than documents with national collaboration. The total number of articles, their normalized citation impact, and the percentage of documents as the corresponding author of academic institutions presented less variation than non-academic institutions. For Brazilian academic institutions, assuming the role of the corresponding author of co-authored articles in Agronomy has little influence on citation impact. As for non-academic institutions, we found an association between the corresponding authorship position within the scope of international collaboration and the higher impact of their scientific production. We point out some potential implications and briefly describe the limitations and future research.
Keywords: Agronomy; Citation impact; Corresponding author; Scientific collaboration